Pandemics, Medicine and Ethics. An Outlook - Reis, Andreas; Schmidhuber, Martina; Frewer, Andreas (Springer Berlin, 2023)
HIV, tuberculosis, SARS, pandemic influenza, MERS-CoV, Zika, Ebola, and now COVID-19: all of these epidemics and pandemics have caused major crises in recent decades, often with far-reaching individual, social, and economic consequences at the national and international levels. The epidemics and pandemics of recent years have underlined the crucial role that the discipline of health ethics/public health ethics can play in policy advice and development as well as in the implementation of socially acceptable options for action. While some ethical questions have already been addressed in individual articles, the present volume attempts to provide a more comprehensive overview of the most important topics. It becomes clear that a certain further development of the discipline of health ethics is necessary, accompanied by increased investments from the side of politics and academic institutions, in order to be better prepared for future crises. On the micro level, for example, the nationwide establishment of clinical ethics committees in all hospitals is a major desideratum, on the meso level the establishment of committees for ethics in healthcare and on the national level there are still greater investments to be made to strengthen existing or newly established national ethics committees. Since many urgent ethical questions—for example, vaccine distribution and travel restrictions—cannot be solved at the national level alone, the international cooperation of national ethics committees must be further strengthened, both regionally and globally. In addition, ethics must be much more integrated into pandemic preparedness measures, and the existence of an “ethics infrastructure”, i.e. clinical ethics committees, research ethics committees and national ethics committees, must be included as an essential indicator for good pandemic planning in corresponding monitoring and evaluation (M&E) instruments.
CRIS-Team Scopus Importer:2024-06-28